KAJIAN KRITIS PEMIKIRAN ABU YUSUF TERHADAP PERKEMBANGAN EKONOMI ISLAM MODERN - Syamsul Rijal; Harjoni Desky; Angga Syahputra (IAIN Lhokseumawe, 2021)
The long journey of the Islamic economic system is interesting to study. Many figures have contributed to the journey of this system, including one of them is Abu Yusuf. Abu Yusuf is an Islamic economic thinker who has made a major contribution to the development of modern Islamic economics. He has introduced the basic principles of Islamic economics as contained in his writings on taxes, administration of tax collection, infrastructure improvements and the concept of prices that go beyond the concept of price in Adam Smith's theory in his work The Wealth of Nations. Abu Yusuf also discussed several measures for economic development and community welfare. No less important, the theme of Abu Yusuf's economic thought is the emphasis on the responsibility of rulers to their people and the Kitab al-Kharaj is authentic evidence of the existence of public finance in Islam, and clearly precedes the conventional theories that exist today.